Community program for managing wetland environment: Case study of Banjarmasin riverbanks - Huda, Nurul; Mariatul Kiptiah (Universitas Negeri Yogyakarta, 2025)
This study examines community initiatives in the management of wetland ecosystems, with an emphasis on riverbanks in Banjarmasin City. Wetland environmental management presents various challenges. The extent of knowledge and community engagement constitutes a challenge in environmental maintenance and management. This study seeks to evaluate current community programs focused on the sustainable preservation, management, and utilisation of wetland environments along the riverbanks of Banjarmasin City. This study employs a case study methodology, utilising data collection techniques that include direct observation at the site, interviews with community members, youth, and local government officials, as well as documentary analysis. The study's findings indicate that community and youth engagement, comprehensive governmental support, and the integration of knowledge with effective practices are essential for the program's success. The rise of environmental activist communities exemplifies the success of community programs in environmental management. In executing the program to manage the wetland ecosystem, both the community and government encounter numerous challenges, including tourists seeking river tours who lack a comprehensive understanding of environmental stewardship along the Banjarmasin City Riverbanks.